Environmental damage news and stock returns: Evidence from Latin America - Eduardo A. Cavallo; Ana Cepeda; Ugo Panizza (Graduate Institute of International and Development Studies, 2024)
This paper studies the interplay between environmental performance and financial valuation of firms in Latin America and the Caribbean. We provide insights into how environmental considerations are integrated into financial decision-making and investor behavior by analyzing the stock market reaction to environmental news of firms with different levels of carbon emission intensity. We find that high emission intensity firms tend to underperform after the release of environmental damage news. Our baseline estimates indicate that, after the release of such news, firms at the 75th percentile of the distribution of emission intensity experience stock returns that are 17% lower than those of firms at the 25th percentile of the distribution of emission intensity. These results suggest that investors care about and price carbon risk, but only when this risk is salient.
Keywords: G12; G14; G18; G32; G38; Q54; 330; Carbon emissions; Climate change; Environmental news; Stock returns